Manajemen Komunikasi Digital Agency pada Program Jong Kreatif - Allfin Dyana Permata; Mochamad Rochim (UNISBA Press, 2022)
Abstract. Along with the development of the times and human knowledge in the field of information exchange, a lot of information circulating today is the fruit of the effects of globalization that will not stop processing. Modern humans will not be able to escape the need for social processes to obtain information that brings changes in the dynamics of social life. The shift in people's social behavior in various fields is at least influenced by massive information technology. In this case, the Telecommunications and Information Accessibility Agency of the Ministry of Communication and Information (BAKTI Kominfo) plays an important role in supporting the distribution of communication and information technology in areas that are still rarely touched by modern technology. Through the Digital Agency, namely the Karya Bangsa Alkademi Foundation, BAKTI Kominfo in collaboration with the Ministry of Education and Culture (Kemendikbud) held the